Heart Rate Methods Can Be Valid for Estimating Intensity Spectrums of Oxygen Uptake in Field Exercise - Salier Eriksson, Jane; Olsson, Karin S. E.; Rosdahl, Hans; Schantz, Peter (Frontiers in Physiology, 2021)
Purpose Quantifying intensities of physical activities through measuring oxygen uptake (V̇O2) is of importance for understanding the relation between human movement, health and performance. This can in principle be estimated by the heart rate (HR) method, based on the linear relationship between HR and V̇O2 established in the laboratory. It needs, however, to be explored whether HR methods, based on HR-V̇O2 relationships determined in the laboratory, are valid for estimating spectrums of V̇O2 in field exercise. We hereby initiate such studies, and use cycle commuting as the form of exercise. Methods Ten male and ten female commuter cyclists underwent measurements of HR and V̇O2 while performing ergometer cycling in a laboratory and a normal cycle commute in the metropolitan area of Stockholm County, Sweden. Two models of individual HR-V̇O2 relationships were established in the laboratory through linear regression equations. Model 1 included three submaximal work rates, whereas model 2 also involved a maximal work rate. The HR-V̇O2 regression equations of the two models were then used to estimate V̇O2 at six positions of field HR: five means of quintiles and the mean of the whole commute. The estimations obtained were for both models compared with the measured V̇O2. Results The measured quintile range during commuting cycling was about 45–80% of V̇O2max. Overall, there was a high resemblance between the estimated and measured V̇O2, without any significant absolute differences in either males or females (range of all differences: −0.03–0.20 L⋅min–1). Simultaneously, rather large individual differences were noted. Conclusion The present HR methods are valid at group level for estimating V̇O2 of cycle commuting characterized by relatively wide spectrums of exercise intensities. To further the understanding of the external validity of the HR method, there is a need for studying other forms of field exercises.